Performance in a pandemic - Bissell, Laura; Weir, Lucy
"This edited collection gathers UK and international artists, academics, practitioners and researchers in the fields of contemporary performance, dance and live art to offer creative-critical responses to the impact of the COVID-19 pandemic on their work. Themes addressed in these case studies include the ways in which liveness functions across digital platforms, the new demands on audiences and performance-makers, those artists and makers who can't or won't move their practice online, and the impact on international festivals as the digital removes geographical and locational restrictions. Brought together, these examples capture the creative activity and output that this unexpected cultural moment has provoked. Creative-critical responses interrogate what the global pandemic has taught us about what it is to make live work during lockdown, and explore what the future of performance-making in a post-Covid world might look like. For all scholars and performance makers whose work brings them into the sphere of contemporary art and culture, this is an essential and stimulating account of practice at the beginning of the 2020s"--
Includes bibliographical references.
Keywords: COVID-19 (Disease) and the arts